TIPE KEPRIBADIAN PADA KARAKTER UTAMA DALAM NOVELA THESTRANGE CASE OF DR. JEKYLL AND MR. HYDE KARYA ROBERT L. STEVENSON - LUMI, JULIO GABRIELL ELIA; MARENTEK, ANDRIYANI; WANTASEN, ISNAWATI L. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â  This research is entitled â€Tipe Kepribadian pada Karakter Utama dalam Novela The Strange Case of Dr Jekyll and Mr Hyde karya Robert L Stevenson.â€ There are two types of personality stated by Jung, which are extraversion and introversion. In addition, Jung explained about the four factors that are applied in the extraversion and introversion. The writer applies the types of personality theory in the novella. The purposes of this research are to identify, classify, and analyze the main character types of personality, and to analyze the factors that influenced these types. The results show that both of the main characters have the extraversion and introversion, but Dr Jekyll dominantly has introversion type and Mr Hyde has extraversion type. The four factors which are explained by Jung also found in both of the main characters, but each character has one dominant factor. Dr Jekyll has more thinking factor, and the other hand Mr Hyde has more sensation factor.Â Key Words: types of personality, extraversion, introversion, Jung